Math, asked by mubashirayaz44, 7 months ago

If x is eliminated from the equations x + b = 0 and x + c = 0 the relation becomes:

A. b / c + 1 = 0
B. b = c
C. b + c = 0
D. b c = 0

Answers

Answered by arnabduttasnt2580
10

Answer:

Answer: B

Step-by-step explanation:

expression : x+b=0

x+c=0

after eliminating x ,

b=0

c=0

then, b=c

Hence Option B is the correct answer.

HOPE IT HELPS...

Answered by Sriji246
1

Answer:

(B) b=c

Step-by-step explanation:

Given equations are:

 \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: x + b = 0

and

 \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  x + c = 0

Let

x + b = 0...............(1) \\x + c = 0................(2)

Eliminate x from the equation (1) and (2),

subtracting the equation (2) from equation (1)

(x + b) - (x + c) = 0 \\ \:  \:  \:  \:  \:  \:  \:  x + b - x - c = 0 \\  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: b - c = 0 \:  \:  \:  \:  \: \\  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: b = c

Therefore, b=c

Hence, the correct option is (B) b=c.

Similar questions